The Protestant Fiscal Ethic: Religious Confession and Euro Skepticism in Germany - Matthias Krapf; Adrian Chadi (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
During the European sovereign debt crisis, most countries that ran into fiscal trouble had Catholic majorities, whereas countries with Protestant majorities were able to avoid fiscal problems. Survey data show that, within Germany, views on the euro crisis differ between Protestants and Non-Protestants, too. Concerns about the euro crisis have increased among Protestants during the crisis, and significantly reduce their subjective wellbeing only. We use the timing of survey interviews and news events in 2011 to account for the endogeneity of euro concerns. Emphasis on moral hazard concerns in Protestant theology may, thus, still shape economic preferences.
Keywords: Z10; I31; E00; 330